Financial econometrics modeling : market microstructure, factor models and financial risk measures - Gregoriou, Greg N., 1956-; Pascalau, Razvan (Houndmills, Basingstoke ; New York : Palgrave Macmillan, 2011)
This book proposes new methods to build optimal portfolios and to analyze market liquidity and volatility under market microstructure effects, as well as new financial risk measures using parametric and non-parametric techniques. In particular, it investigates the market microstructure of foreign exchange and futures markets.
Includes bibliographical references and index.
oif 16/09/14
Loan
Keywords: Econometrics; Finance -- Mathematical models; Financial risk management -- Mathematical models